An unbalanced‐to‐balanced diplexer based on substrate integrated waveguide cavity. Issue 2 (16th September 2014) - Chu, Hui; Peng, Li; Jin, Chen; Chen, Jian‐Xin
ABSTRACT A novel unbalanced‐to‐balanced diplexer based on a dual‐mode substrate integrated waveguide (SIW) cavity is proposed and implemented. The diplexer is realized using one dual‐mode cavity and two single‐mode cavities. By properly choosing, feeding and coupling the cavity operating at the TE102 or TE201 mode, so as to not only provide capabilities to realize the desired unbalanced‐to‐balanced transmission within both Rx and Tx channels but also realize good differential‐mode channel‐to‐channel isolation. To the author's knowledge, we present for the first time an unbalanced‐to‐balanced type diplexer based on the application of SIW. The proposed diplexer was successfully designed, simulated, and fabricated. Good agreement can be observed between simulated and measured performances in our letter. The measured in‐band common‐mode rejection is better than 33 dB for both channels. A minimum differential‐mode isolation of about 50 dB across the Rx band and about 40 dB across the Tx band is also observed in the measurement. © 2014 Wiley Periodicals, Inc. Int J RF and Microwave CAE 25:173–177, 2015.